A national facility for biological cryo‐electron microscopy. (1st January 2015) - Saibil, Helen R.; Grünewald, Kay; Stuart, David I.
<x xml:space="preserve">Abstract</x> Three‐dimensional electron microscopy is an enormously powerful tool for structural biologists. It is now able to provide an understanding of the molecular machinery of cells, disease processes and the actions of pathogenic organisms from atomic detail through to the cellular context. However, cutting‐edge research in this field requires very substantial resources for equipment, infrastructure and expertise. Here, a brief overview is provided of the plans for a UK national three‐dimensional electron‐microscopy facility for integrated structural biology to enable internationally leading research on the machinery of life. State‐of‐the‐art equipment operated with expert support will be provided, optimized for both atomic‐level single‐particle analysis of purified macromolecules and complexes and for tomography of cell sections. The access to and organization of the facility will be modelled on the highly successful macromolecular crystallography (MX) synchrotron beamlines, and will be embedded at the Diamond Light Source, facilitating the development of user‐friendly workflows providing near‐real‐time experimental feedback.